Vocabulary for Lower Back and Lumbar Pain in Russian Dialects: an Overview - E. L. Berezovich; M. O. Leontyeva (Научный диалог, 2021)
The semantic-motivational and etymological analysis of the Russian dialectal designations of lumbar and lumbar pain is presented. The material was extracted from dictionaries of Russian dialects, from unpublished card files of the Ural University toponymic expedition to the territories of the Russian North and the Upper Volga region, as well as folklore and ethnographic sources related to folk medicine. The main semantic-motivational models underlying the designation of the lower back, which can reflect the idea of the “topography” of this part of the body, correlation with adjacent bodily areas, the functions of the lower back, and pain symptoms are considered. It is noted that in the “lumbar” vocabulary the main place belongs to the names of lumbar pain, the abundance of which is determined by the nature of agricultural labor. It has been shown that several names contain an indication of the localization of pain, but in most cases the nature of the pain is conveyed — cutting, stabbing, aching, etc. The authors analyze linguistic material in combination with folklore and ethnographic: texts of conspiracies, ritual dialogues, descriptions of magical healing practices. Sign complexes are identified, within which the designations of pain symptoms are projected onto methods, means and tools of treatment. In such complexes, the principle of etymological magic can be realized, consistent with the concept of the “witchcraft” origin of pain symptoms. Motivational and etymological solutions for dark words are proposed.